Plasticity of foraging strategies in the blue tit, Cyanistes caeruleus and the domestic chick, Gallus gallus domesticus - Mc Mahon, Keith (Trinity College (Dublin, Ireland). Department of Zoology, 2014)
This research was primarily concerned with dietary conservatism in wild blue tits, Cyanistes caeruleus. Dietary conservatism refers to the tendency for some individuals of a population to ignore novel foods. Dietary conservatism has been found to occur in a number of species of birds and fish. Previous studies into dietary conservatism have only been concerned with the presence or absence of the behaviour and its consequences for populations of novel prey species. These studies have shown that while there are individuals who readily accept novel food, adventurous consumers (AC), there are a number of individuals in the population who continue to refuse to accept novel food, these individual are referred to as being dietary conservative or DC.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin